TOOLKIT FOR PROMOTING THE SYSTEMIC DEVELOPMENT OF HEALTH CARE INSTITUTIONS AT THE LOCAL LEVEL - VASYLTSIV, Taras; BILETSKA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the study, attention is updated to the problem of stimulating the development of small entrepreneurship at the local level and simultaneously improving the system of providing social services to the local population, in particular medical care. It was emphasized that stimulating the development of small business entities and also the medical sector in rural and remote areas is a very difficult task that requires identification in the implementation of specific tools and the involvement of sufficient resources for such purposes. It has been proven that this is why research in this field is always unique and has a high theoretical, methodological and applied value. The purpose of the study is to improve the theoretical, methodological and applied principles of forming policy tools for supporting and stimulating the development of small entrepreneurship in the medical field at the local level. It is shown that the decentralization reform, which is being implemented with permanent success in Ukraine, has largely shifted from the central to the local level the issue of management and financial and resource provision of local social and economic development. These issues become particularly acute in the field of medicine, and often local self-government bodies are objectively unable to solve these extremely difficult tasks on their own. It is necessary to use non-traditional methods and approaches. One of these can be the stimulation of private business in the form of small private health care institutions that provide a wide range of diagnostic and preventive medical services to the population. It was concluded that the policy of local self-government bodies in terms of promoting the development of small business initiatives in the field of providing medical services to the population should be broad in nature, in particular aimed at the general socio-economic development of small towns and surrounding rural areas. Conceptually, the principles of such a policy can be implemented in the following directions: development of production factors; creation and improvement of small business support infrastructure; formation of solvent demand due to increased employment and incomes of the population; development of priority sectors of the economy; increasing the efficiency of small enterprises in the medical field.